Influence of pH value on particle morphology and electrochemical properties of LiFePO4/C by biosynthesis method. (27th July 2019) - Cao, Yue; Feng, Wangjun; Su, Wenxiao; Chen, Linjing; Song, Changkun; Li, Miaomiao
Abstract: A series of LiFePO4 /C composites are prepared under the conditions of pH = 3, 5, 7, 8, 9 via biosynthesis method. The X-ray diffraction demonstrates that all of well-crystallized LiFePO4 /C composites can be successfully prepared by adjusting the pH value. The images of scanning electron microscopy show that the structure and size of different samples have obvious changes. Besides, the LiFePO4 /C composite prepared at the value of 8 delivers a best discharge capacity of 158.7 mAh/g at 0.1 C. The results show that the electrochemical performance of LiFePO4 /C composites is governed by pH value.